Bio‐banking gut microbiome samples. (9th June 2016) - Bolan, Shankar; Seshadri, Balaji; Talley, Nicholas J; Naidu, Ravi
Abstract : An increasing number of academic and private biobanks store faecal samples for research and stool transplantation purposes. As stool samples are unique from other biological tissues and materials, stool biobanks require appropriate regulation and additional research on gut microbiota to ensure safe application in the clinic.